Adult size and timing of reproduction in five species of Asobara parasitoid wasps. (14th November 2019) - Askari Seyahooei, Majeed; Kraaijeveld, Ken; Bagheri, Abdoolnabi; van Alphen, Jacques J. M.
Abstract: The majority of adult parasitoid wasps are unable to synthesize lipids and therefore face a trade‐off between the investment of lipids in eggs or in the maintenance of soma. It has been shown that resource allocation should depend on body size in parasitoids. Given that smaller females have shorter expected life times, they should concentrate their reproductive effort into early life. To test this prediction, we investigated the relationship between body size and the timing of egg production in parasitoids. We measured body size, lipid reserves, and reproductive investment (number of eggs, ovigeny index equivalent [OIE] and egg size) at eclosion in five species of Asobara (Hymenoptera: Braconidae) originating from different geographic and climatic environments. Our results show significant interspecific variation in all these traits. A diagnostic test for phylogenetic independence revealed that closely related species did not resemble each other more closely than expected by chance for all traits measured. Lipid reserves scaled positively with body size both between and within species. In agreement with theory, OI correlated negatively with body size both between and within species. Total egg area at eclosion correlated negatively with lipid reserves both between and within species. This indicates the existence of a trade‐off between allocation of lipids to current reproduction and survival/future reproduction. With the exception of the most extreme pro‐ovigenic species, A. persimilis, we found that pro‐ovigeny was compensated for by small egg size. Our results indicate the role of habitats in shaping interspecific variation in resource allocation strategies.